Two New Species of the Genus Candelariella from China and Korea. Issue 1 (2nd January 2019) - Liu, Dong; Wang, Lisong; Wang, Xin Yu; Hur, Jae-Seoun
Abstract: Candelariella is a widespread lineage of lichenized ascomycetes with ambiguous relationships among species that have not solved completely. In this study, several specimens belonging to Candelariella were collected from China and South Korea, and the internal transcribed spacer region was generated to confirm the system position of the newly collected specimens. Combined with a morphological examination and phylogenetic analysis, two new areolate species, Candelariella rubrisoli and C. subsquamulosa, are new to science. Detail descriptions of each new species are presented. In addition, C. canadensis is firstly reported from China mainland.